Demand Characteristics Confound the Rubber Hand Illusion - Peter Lush (Collabra: Psychology, 2020)
Reports of experiences of ownership over a fake hand following simple multisensory stimulation (the ‘rubber hand illusion’) have generated an expansive literature. Because such reports might reflect suggestion effects, demand characteristics are routinely controlled for by contrasting agreement ratings for ‘illusion’ and ‘control’ conditions. However, these methods have never been validated, and recent evidence that response to imaginative suggestion (‘phenomenological control’) predicts illusion report prompts reconsideration of their efficacy. A crucial assumption of the standard approach is that demand characteristics are matched across conditions. Here, a quasi-experiment design was employed to test demand characteristics in rubber hand illusion reports. Participants were provided with information about the rubber hand illusion procedure (text description and video demonstration) and recorded expectancies for standard ‘illusion’ and ‘control’ statements. Expectancies for ‘control’ and ‘illusion’ statements in synchronous and asynchronous conditions were found to differ similarly to published illusion reports. Therefore, rubber hand illusion control methods which have been in use for 22 years are not fit for purpose. Because demand characteristics have not been controlled in illusion report in existing studies, the illusion may be, partially or entirely, a suggestion effect. Methods to develop robust controls are proposed. That confounding demand characteristics have been overlooked for decades may be attributable to a lack of awareness that demand characteristics can drive experience in psychological science.